Title: Impact of Burnout and Work Environment on Quality of Care and Registered Nurse’s job Satisfaction and Retention in Saudi Arabia - Alotaibi, Fahad; Moussa, Mahaman (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2016)
To investigate the impact of burnout and work environment on job satisfaction, intentto leave, quality of care among Registered Nurses in Saudi Arabia. Background: A healthywork environment plays a critical role in health care system. This research enhances a greaterunderstanding how the work environment and burnout play a critical role in the quality ofpatient care, intent to leave and job satisfaction among nursing professionals.